Analysis of outcomes of single‐unit cord blood transplantation with umbilical cord blood units processed with two different red blood cell sedimentation reagents. Issue 6 (20th May 2021) - Babic, Aleksandar; Buchanan, Paula; Gill, Ammara; Bloomquist, Jenni; Regan, Donna; Bhatla, Deepika; Ferguson, William
Abstract: Background: Various processing methodologies are routinely used to reduce volume and red blood cell content of umbilical cord blood (UCB) units collected for hematopoietic stem cell transplantation. There is limited information regarding effects of UCB processing techniques on clinical outcomes. Study Design and Methods: Retrospective data analysis compared laboratory and clinical outcomes following single‐unit UCB transplantation performed between 1999 and 2015. All UCB units were from St. Louis Cord Blood Bank and all were manually processed with either Hetastarch processed cord blood units (HCB) ( n = 661) or PrepaCyte processed cord blood units (PCB) ( n = 84). Additional sensitivity analysis focused on units transplanted from 2010 to 2015 and included 105 HCB and 84 PCB. Results: There were no significant differences in patient characteristics between the two groups. Pre‐freeze total nucleated and CD34+ cell counts, cell doses/kg of recipient weight, and total colony‐forming units (CFUs) were higher in PCB compared with HCB. Post‐thaw, the PCB group had a significantly better total nucleated cell recovery, while there were no significant differences in cell viability, CFU recovery, or CD34+ cell recovery. Primary analysis demonstrated faster neutrophil and platelet engraftment for PCB but no differences in overall survival (OS), whereas sensitivity analysis found no effect of processing method on engraftment, but better OS in the HCB group compared with PCB group. Conclusion: The UCB processing method had no significant impact on engraftment. However, we cannot completely exclude the effect of processing method on OS. Additional studies may be warranted to investigate the potential impact of the PCB processing method on clinical outcomes.